Budaya dan Kearifan Dakwah - Masykurotus Syarifah (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2016)
When talking about propaganda and cross-cultural communication, there are at least three key words to unravel these issues, namely propaganda, communication, and culture. All of the three have their own meaning and function. Here the need for more in-depth decomposition.Learning cross-cultural communication is necessary because it is a ticket for us to be able to adapt wherever we are, particularly in Indonesia where the various tribes and cultures live together. A prolonged conflict would occur if the person does not understand the differences and does nothing with cross-cultural communication. By studying how to build the cross-cultural communication, people will understand the differences and be neutral or moderate. So the conflict rose among different ethnic cultures will not happen. In addition, studying the cross-cultural communication will make us more cautious in building relationship to the different cultures. Preachers should be able to understand the place, culture, customs, and language of his objects because it will determine the success of their preaching.Keywords: Wisdom, Propaganda, Culture.